Indonesia SMEs: sharing internet, sharing cost to improve the competitiveness - Nurchim,Tri Djoko Santosa (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The successful of Small and Medium Enterprises (SMEs) the main key of economic development in a country. Therefore, SMEs must improve their knowledge about global market. To connect the global market, SMEs can adoption the Information Communication and Technology especially internet infrastructure. But, the adoption of ICT run slowly in Indonesia SMEs. From this condition then necessary to develop internet infrastructure with more efficient costs. This research aim is analyze and develop new alternative to build an internet infrastructure network using Wireless Distribution System (WDS) among SMEs. The process implementation using Action Design Research (ADR) method with case study in two creative SME at Baki, Sukoharjo, Indonesia. As results, SMEs can sharing internet infrastructure and experts in build and operation it so can reduce their cost business operation. Other findings, they can interact among them to increase business innovation and finally they can improve their competitiveness.